2015
DOI: 10.1186/s12891-015-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

The disease-modifying effect of dehydroepiandrosterone in different stages of experimentally induced osteoarthritis: a histomorphometric study

Abstract: BackgroundOsteoarthritis (OA) is likely to become an increasing burden in the coming decades. Various agents have been developed to slow the progression of OA, and are collectively known as ‘disease-modifying drugs’, however, there is still little reliable evidence that such agents will be successful. Dehydroepiandrosterone (DHEA), a sex hormone precursor, has been recently proven as protective agent against OA, but the exact mechanism is still unkown. In the current study, the effects of weekly intra-articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…As previously published, in the macroscopic evaluation of knee joint samples, we noted that the medial compartments showed slightly greater degeneration than the lateral compartments. In addition, femur also demonstrated a slightly greater deterioration than that observed in tibias (42,44). Even though some authors observed that administration of BPs showed a significant improvement in the cartilage surface and a minor number of osteophytes (3,59), in our study, risedronate did not show any improvement in the cartilage condition and did not supress the osteophyte formation.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…As previously published, in the macroscopic evaluation of knee joint samples, we noted that the medial compartments showed slightly greater degeneration than the lateral compartments. In addition, femur also demonstrated a slightly greater deterioration than that observed in tibias (42,44). Even though some authors observed that administration of BPs showed a significant improvement in the cartilage surface and a minor number of osteophytes (3,59), in our study, risedronate did not show any improvement in the cartilage condition and did not supress the osteophyte formation.…”
Section: Discussioncontrasting
confidence: 77%
“…According to previous publications, it seems that early bisphosphonate therapy may help to preserve periarticular bone properties, slowing down the short-term degeneration ( 10 , 23 , 26 ). In OA pathology, histological changes are time-dependent ( 42 ) thus, the time point of treatment initiation is crucial for treating OA and similarly, the efficacy of BPs depends on the disease stage ( 10 , 62 ). In this regard, a more beneficial effect with preventive treatment administration was observed ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the rabbit as an experimental animal model, although their histological osteoarthritic lesions have been extensively studied by the scientific community for numerous years ( 29 , 33 , 42 ), at present, there are still some differences in the parameters analyzed between preclinical studies. With reference to the anatomical location of the pathological changes, Huang et al ( 49 ) pointed out that at 16 weeks after surgery, rabbits showed partial or full thickness cartilage erosion, more marked in the MFC. These results were consistent with the results of other researches, which reported more pronounced degenerative bone changes in the femur and in the medial compartment ( 33 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the protective effects of E2 and DHEAS on OA occurrence are unclear. In a cohort of community-dwelling older subjects, a lower DHEAS was associated with OA irrespective of site and sex (27); and histomorphometric studies in a rabbit model of progressive OA showed that DHEAS treatment reduced cartilage lesions and delayed cartilage degeneration (28,29). DHEAS was shown to modulate the imbalance between matrix metalloproteinases (MMPs) and its inhibitors (30)(31)(32)(33); and intra-articular administration of DHEA reduced aggrecanase expression in vivo (34).…”
Section: Discussionmentioning
confidence: 99%